Towards an Integration of Systems Engineering and Project Management Processes for a Decision Aiding Purpose. Issue 1 (July 2017) - Lachhab, M.; Béler, C.; Solano-Charris, E.L.; Coudert, T.
Abstract: This article proposes an integrated process that combine Systems Engineering processes and Project Management ones. These processes are defined according to the industrial standard processes existing in the literature. The main idea is to define a common information model enabling the federation of all the points of view of the different actors with regards to Systems Engineering, Project Time Management, Project Cost Management and Project Risk Management. The resulting integrated project graph encompasses all the scenarios established after defining all the coupling points between those processes. The definition of the graph is based also on the available knowledge and the capitalized experiences resulting from experience feedback on previous projects. The scenario selection optimization is then performed using a decision-aided tool that aims to build a panel of Pareto-optimal solutions taking into account uncertainties on project objectives (cost and duration). This tool will also enable the decision-maker to select one scenario according to an acceptable level of risks. The integrated process, the optimization tool based on Ant Colony Optimization (ACO) and the method for decision making are described in the paper.